2007
DOI: 10.4049/jimmunol.178.6.3962
|View full text |Cite
|
Sign up to set email alerts
|

T Cell TRAIL Promotes Murine Lupus by Sustaining Effector CD4 Th Cell Numbers and by Inhibiting CD8 CTL Activity

Abstract: T cells play an essential role in driving humoral autoimmunity in lupus. Molecules such as TRAIL exhibit strong T cell modulatory effects and are up-regulated in lupus, raising the possibility that they may influence disease severity. To address this possibility, we examined the role of TRAIL expression on pathogenic T cells in an induced model of murine lupus, the parent-into-F1 (P→F1) model of chronic graft-vs-host disease (GVHD), using wild-type or TRAIL-deficient donor T cells. Results were compared with m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 63 publications
1
35
0
Order By: Relevance
“…Among our observations, a critical point is that helpless memory CD8 T cells exhibit a defect in granzyme B-mediated cytotoxic functions. In this respect, a recent observation suggested that TRAIL expression on CD8 T cells negatively regulates the granzymeB/perforin-mediated CD8 T cell killing (34). This suggests that heterospecific CD4 help to memory CD8 T cell may include a TRAIL-dependent component that could control not only survival but also cytotoxic functions.…”
Section: Discussionmentioning
confidence: 99%
“…Among our observations, a critical point is that helpless memory CD8 T cells exhibit a defect in granzyme B-mediated cytotoxic functions. In this respect, a recent observation suggested that TRAIL expression on CD8 T cells negatively regulates the granzymeB/perforin-mediated CD8 T cell killing (34). This suggests that heterospecific CD4 help to memory CD8 T cell may include a TRAIL-dependent component that could control not only survival but also cytotoxic functions.…”
Section: Discussionmentioning
confidence: 99%
“…Signi fi cant elevation (~20-fold over control) of autoantibodies such as anti-ssDNA can be seen at 4 weeks following the transfer of as few as 8 × 10 6 B6 donor CD4 T cells. More substantial elevations (~75-fold) are seen at 12 × 10 6 CD4 T cells ( 9 ) ; however, renal disease is histologically mild at this dose and typically 15-20 × 10 6 B6 CD4 T cells are required for signi fi cantly elevated glomerular scores ( 11 ) . By contrast, unfractionated DBA splenocytes containing as few as 12-14 × 10 6…”
Section: Introductionmentioning
confidence: 99%
“…P→F1 aGVHD was induced with 50 3 10 6 unfractionated splenocytes from B6 wild-type (WT) or B6 IL-21R 2/2 donors injected i.v. into 6-8-wk old BDF1 mice, as described (34). In some experiments, the number of donor CD4 and CD8 T celquantified first by flow cytometry, and the donor cell number was adjusted so that the amount of CD8 and CD4 T cells in the IL-21R 2/2 donor inoculum was approximately equal to that of WT donor cells.…”
Section: Induction Of Graft-versus-host Disease and In Vivo Il-21 Trementioning
confidence: 99%